PENINGKATAN KESADARAN KEAMANAN SIBER SISWA SMK INSAN CENDEKIA YOGYAKARTA - Yuliansah, Yuliansah; Kustitik, Kustitik; Siregar, Ilham Ramadan Pandu Setia Negara; Dwihartanti, Muslikhah; Sutirman, Sutirman (Universitas Sanata Dharma, 2025)
Advancements in information and communications technology (ICT) have accelerated significantly in the last decade, with key indicators such as artificial intelligence, the Internet of Things, and cloud computing demonstrating a level of technological development far surpassing previous years. This progress has provided substantial benefits to society, enhancing the efficiency and accessibility of information across various sectors. However, these technological advances also present challenges, particularly concerning increasingly complex cybercrimes that are frequently encountered by Generation Z as active internet users. Community service activities were conducted at Vocational High School Insan Cendekia Yogyakarta on June 11-12, 2024, aiming to increase the students’ awareness of cybersecurity and digital literacy. The activities included lectures, demonstrations, and discussions on cybercrime and digital literacy, involving 35 participants. Results from pretests and posttests indicated a significant improvement in participants' knowledge, with an average score increase of 11.43 points or 16.8%. Participant satisfaction surveys also revealed that the activity was highly beneficial and met expectations. Overall, the activity successfully achieved its primary objective of enhancing students' awareness and knowledge about cybersecurity, evidenced by high levels of participation and satisfaction.